Landasan dan Asas Pengembangan Kurikulum dalam Sistem Pendidikan - Harjun Harjun; Muliha Halim; Hasniah Hasniah; Layly Ambar Vyuta Widodo (Kayee: Jurnal Pendidikan dan Ilmu Sosial, 2026)
This research examines the foundations and principles of curriculum development within the education system. This research employed a qualitative method with a literature review approach. The study found that the evolution of the curriculum in Indonesia, from a more adaptive and student-focused approach, such as the Independent Curriculum, demonstrates a continuous effort to improve the quality of education to better meet global challenges. Therefore, the success of curriculum development depends heavily on the alignment between the foundations and principles applied, as well as the ability to implement them contextually in the field. A well-designed and systematic curriculum will produce students who are competent, have character, and are ready to face dynamic changes in the future.